Fabrication of Kevlar®-reinforced ultra-high molecular weight polyethylene composite through microwave-assisted compression molding for body armor applications. (April 2021) - Guleria, Taresh; Verma, Nishant; Zafar, Sunny; Jain, Vivek
Kevlar®-reinforced composites are used in high energy absorption applications. In the present work, Kevlar®-reinforced ultra-high molecular weight polyethylene composites were fabricated through microwave-assisted compression molding. The microwave-assisted compression molding parameters were optimized through trial and error method. Analysis of mechanical behavior of composites was accessed through uniaxial tensile testing, flexural testing, impact testing, and nano-indentation. The fractured specimens were observed using scanning electron microscopy. An increment of 92.2% was observed in the ultimate tensile strength of the ultra-high molecular weight polyethylene/Kevlar® composite compared to neat ultra-high molecular weight polyethylene. Flexural properties, impact energy absorption rate, and hardness property of the composite were increased by 27.1%, 91.6%, and 4.77%, respectively, compared to pure ultra-high molecular weight polyethylene. Enhanced mechanical properties may be attributed to unique microwave heating phenomena during microwave-assisted compression molding.